A New Treaty for Fully Autonomous Weapons: A Need or a Want? - Maskun, Maskun; Ramli, Rafika Nurul Hamdani (Faculty of Law, Hasanuddin University, 2018)
Autonomous Weapon System (AWS) is still discussed and is considered to the principle of International Humanitarian Law (IHL) particular the principle of distinction and proportionality. In line with moral and ethical issues, some experts and global citizens agree that AWS will likely to distract moral and ethical on a battlefield and are never able to replace human’s feeling. Human beings are responsible over AWS because there is no such a fully autonomous weapons exist. It is always a human commander behind the actions. To bridge the situation on discussion of AWS, a new treaty should be created in order to anticipate further violation.